NIO-1, A Novel Inhibitor of OCT1, Enhances the Antitumor Action of Radiofrequency Ablation against Hepatocellular Carcinoma - Yang, Hua; Yang, Yang; Zou, Xiaozheng; Zhang, Qian; Li, Xiaoli; Zhang, Chunyu; Wang, Yanan; Ren, Lili (Current Molecular Medicine, 2024)
Background: Radiofrequency ablation (RFA) is an important treatment strategy for patients with advanced hepatocellular carcinoma (HCC). However, its therapeutic effect is unsatisfactory and recurrence often occurs after RFA treatment. The octamer-binding transcription factor OCT1 is a novel tumour-promoting factor and an ideal target for HCC therapy. Objective: This study aimed to expand the understanding of HCC regulation by OCT1. Methods: The expression levels of the target genes were examined using qPCR. The inhibitory effects of a novel inhibitor of OCT1 (NIO-1) on HCC cells and OCT1 activation were examined using Chromatin immunoprecipitation or cell survival assays. RFA was performed in a subcutaneous tumour model of nude mice. Results: Patients with high OCT1 expression in the tumour tissue had a poor prognosis after RFA treatment (n = 81). The NIO-1 showed antitumor activity against HCC cells and downregulated the expression of the downstream genes of OCT1 in HCC cells, including those associated with cell proliferation (matrix metalloproteinase-3) and epithelial-mesenchymal transition-related factors (Snail, Twist, N-cadherin, and vimentin). In a subcutaneous murine model of HCC, NIO-1 enhanced the effect of RFA treatment on HCC tissues (n = 8 for NIO-1 and n = 10 for NIO-1 + RFA). Conclusion: This study demonstrated the clinical importance of OCT1 expression in HCC for the first time. Our findings also revealed that NIO-1 aids RFA therapy by targeting OCT1.
Keywords: radiofrequency ablation